Stable platform means better player - Peterson, C.; Nittinger, N. (Medicine and Science in Tennis, 2009)
Physiotherapists, physicians, coaches and fitness trainers are all well aware of the importance of upper and lower ´core stability´ training to a player`s overall development, performance and injury prevention. A healthy back must be associated with good flexibility and strong upper and lower core platform for the extremities to move off of. The purpose of all ´core stability programs is to create a stable base of support.